Tiki-taka algorithm: a novel metaheuristic inspired by football playing style - Mohd Fadzil Faisae, Ab Rashid (Emerald Group Publishing Ltd., 2021)
Purpose Metaheuristic algorithms have been commonly used as an optimisation tool in various fields. However, optimisation of real-world problems has become increasingly challenging with to increase in system complexity. This situation has become a pull factor to introduce an efficient metaheuristic. This study aims to propose a novel sport-inspired algorithm based on a football playing style called tiki-taka.